HUMAN–LONG-TAILED MACAQUE INTERACTIONS AND ECOTOURISM POTENTIAL IN THE GUNUNG KERIANG RECREATIONAL PARK, KEDAH, PENINSULAR MALAYSIA - N. E. A. Taufet-Rosdi; B. M. Md-Zain (Journal of Animal and Plant Sciences, 2023)
The long-tailed macaque (Macaca fascicularis) is among the Cercopithecidae primates that can be found in Gunung Keriang Recreational Park (GKRP), Kedah, Peninsular Malaysia. Its population size, human–primate interactions, and public perceptions have never been revealed. This study aimed to estimate the population size, evaluate interactions between macaques and visitors, determine the perception of visitors and locals toward primates, and assess the potential of GKRP as ecotourism site. The population size of long-tailed macaques was estimated through census walk, whereas the interactions between visitors and macaques were evaluated through scanning sampling technique. The perception of visitors and local people and the potential of GKRP as ecotourism site were determined through a questionnaire. Results indicated that 72 individuals of M. fascicularis were found ranging in GKRP. The interactions between visitors and macaques in GKRP were primarily constituted of positive interactions. Contrast perceptions between visitors and local people toward GKRP primates were obtained that were due to different experiences with primates encountered by both respondent groups. Visitors were inclined to accept macaques, whereas a majority of locals dislike them. GKRP has a potential to become an established ecotourism site considering values this recreational park has given to the visitors. Research findings were anticipated to increase the knowledge on human–primate interactions and ecotourism management that ultimately contributed toward the management of long-tailed macaques and their natural habitat.
Keywords: Macaca fascicularis; long-tailed macaques; human–primate interaction; ecotourism